Deadlock in corporate governance: Finding a common strategy for private telephone companies, 1978–1998. Issue 6 (18th August 2018) - Nevalainen, Pasi
Abstract: This paper looks at how a group of small, incumbent private telephone companies complied with the international convergence of market structures. The existing research has mainly focused on large national incumbents, assuming a transition to multinational enterprise. This development process is often associated with privatisation policies and various institutional factors. The article tests these assumptions using a case study of the network of Finnish local telephone companies. It looks at the development of an interfirm network, its perspectives on the different phases of the deregulation process, and how the network tried to regenerate itself but failed to form a unified corporate structure capable of mounting a common business strategy. The reason for this failure resembles the idea of governance inseparability : private telecom companies were committed to the objectives and form of a tried and trusted cooperation model, which no longer met the requirements of the competitive and increasingly liberalised business environment of the 1990s. This case demonstrates that the significance of both corporate governance and organisational development are, above all, related to the firm's ability to regenerate itself.